FOCUS ON FORM IN 2013 JUNIOR HIGH SCHOOL CURRICULUM (RETAIN, 2014)
FOCUS ON FORM IN 2013 JUNIOR HIGH SCHOOL CURRICULUM Windya Firdayani Ariza English Education, Faculty of Languages and Arts, State University of Surabaya Win_dya_chub2y@yahoo.com Ahmad Munir English Education, Faculty of Languages and Art, State University of Surabaya Munstkip@yahoo.com Abstrak Kurikulum 2013 adalah kurikulum yang saat ini dilaksanakan di Indonesia. Penelitian ini bertujuan untuk menggambarkan fokus guru dalam mengajar tata bahasa apakah itu berfokus pada bentuk atau makna dan menggambarkan perasaan siswa dalam belajar tata bahasa apakah mereka merasa belajar atau tidak. Penelitian ini adalah kualitatif. Para peserta penelitian ini adalah seorang guru bahasa Inggris dan siswa kelas pertama SMPN 1 Gresik. Dua instrumen yang digunakan untuk mengumpulkan data yaitu: observasi dalam bentuk rekaman video guru dan kegiatan siswa di kelas dan merekam video dari diskusi kelompok. Ini digunakan untuk merekam cara guru dalam menggabungkan tata bahasa pada kurikulum 2013 dan kegiatan siswa. Rekaman video dari diskusi kelompok digunakan untuk merekam perasaan siswa. Ditemukan bahwa guru fokus pada bentuk. Dia menekankan pada aturan tata bahasa. Ditemukan pula bahwa siswa merasa belajar tata bahasa oleh guru. Kesimpulannya, guru menerapkan focus pada bentuk di kurikulum 2013. Itu terjadi di kelas dimana peneliti mengamat, bahwa guru menjelaskan materi yang lebih jelas kepada siswa berdasarkan konstruk bahasa dan aturan tata bahasa. Kesimpulan lain adalah bahwa guru tidak mengikuti aturan kurikulum 2013. Pada 2013 kurikulum adalah fokus pada makna. Kata Kunci: Fokus pada bentuk, tata bahasa, kurikulum 2013 Abstract The 2013 curriculum is the current curriculum that was implemented in Indonesia. This study focused its goal to describe the teacher’s focus in teaching grammar whether it focuses on form or on meaning and describe the students’ feeling in learning grammar whether they experienced or not. This study was qualitative. The participants of this study were an English teacher and the first graders of SMPN 1 Gresik. Two instruments were used to collect data namely: Observation in the form of video recording of teacher and students’ activities in classroom and video recording of focused group discussion. It used to record the teacher’s way in incorporating grammar in 2013 curriculum and the students’ activities. Video recording of focused group discussion used to record the feeling of students. It was found that teacher focused on form. She concerned on grammatical rule. It was also found that the student experienced to learn grammar by the teacher. In conclusion, the teacher interpreted grammar in 2013 curriculum by focusing on form. It happened in the classroom which the researcher observed, that the teacher explained the materials more clearly to the students based on the construct of language and grammatical rule. Another conclusion is that the teacher did not follow the rule of 2013 curriculum. In 2013 curriculum is focus on meaning.. Keywords: Focus on Form, grammar, 2013 curriculum INTRODUCTION 2013 Curriculum is the current curriculum that is released on July 13th 2013 by the government in Indonesia. This curriculum is a continuation of KBK (Kurikulum Berbasis Kompetensi) that was released at 2004 that cover attitude, knowledge and skill competence integrated. 2013 curriculum has four Kompetensi Inti. Kompetensi Inti is applicable to all the subjects. It is as the bond of all students’ competencies that are produced in each subject. The contents are the same between English and other subjects, but the differences are on the Kompetensi Dasar for each Kompetensi Inti. For English, especially grammar the point in Kompetensi Dasar is in the third. It is Memahami fungsi social, struktur teks dan unsur kebahasaan (Kemendikbud, 2013a). It means that the students have to achieve those three things to make them competence in English. According to curriculum 2006, there are three important aspects considered when people think of language. They are context, text and language. The purpose of social function is the reason why we speak or write in the context. Organization structure of the text or generic structure is the text organization or text arrangement. Language features or lexical that is such things as the grammar vocabulary and connectors that we use. Social function, organization structure and language feature above are associated with Genre Based Approach. Genre Based Approach is recommended approach that is based on curriculum. Genre Based Approach is used to conduct the classroom activity. According to Yan (2005), this approach has become popular since the 1980s along with the notion that students writers could benefit from studying different types of written text. In Genre Based Approach, teaching and learning focuses on the understanding and production of selected genres of texts (Lin, 2006). Learning around texts genres has been increasingly influential in main stream ELT in a number of situations, including primary, secondary, tertiary, professional and community teaching context involving native speaker of English as well as ESL and EFL learners. It shows that Genre Based Approach is powerful response to the deficit of process models (Gao, 2007). Genre Based Approach starts with the whole text as the unit in focus, rather than the sentence. The focus on the whole implies that there is higher level of order and patterning in language than just in sentence-grammar at the level of discourse organization and meta-patterning of grammatical features. In Indonesia, according to curriculum 2006 Genre Based Approach is conducted in two cycles; they are spoken and written cycle. It is because at the end of spoken cycles, students are expected to be able to produce monologue in the same of genre that they are learning. Similarly, at the end of written cycle every students must be able to produce written text of genre that they are learning (Astaman, 2010). For instance, if the genre is narrative, at the end of written cycle every student must be able to write a narrative text or to tell a narrative story. It is also strengthened by Callaghan(1988), that genre is should be classified to be two aspects. First, genre is classified as spoken genre and the second genre is classified as written genre. It means that genre as spoken has the reason as language is said to be functional, because its organization quite fundamentally reveals the purpose for which any natural language came. Meanwhile genre as written has reason as language is to be understood as text, any meaningful passage of language that serves some social purpose. Grammar commonly taught based on focus on form and focus on meaning. Focus on form means the students have to aware on grammatical form of the language. According to Long (1997) Focus on form is a method for composing sentence based on the right pattern. It promotes the acquisition of specific language form such as grammar and the meaning of words in the meaning-based second language activity. Doughty & Williams (1999) state that state that a focus on the form (FonF) of the language consists of drawing the learner's attention to the linguistic features of the language. Thus, a focus on form approach would allow for the second language (L2) learners to concentrate on the grammatical rules and construct of the language. For example, a student is given a text in the L2. He or she would focus on form if they were asked to analyze the text in terms of how it represents the rules of the language. Other reason, she wants to develop the language knowledge and language acquisition. This condition proves the theory from Long & Robinson (1999) that focus on form as an occasional shift of attention to linguistic code features by the teacher and/or one or more students triggered by perceived problems with comprehension or production. He also states that Focus on form is a basis of Interaction Hypothesis and it emphases the importance of interaction between learners and other speakers in order to develop their language knowledge. It has to depend on the structure. Focus on meaning would be concerned with getting L2 learner to concentrate solely on understanding the message being conveyed. Focus on meaning means emphasize on the meaning of a language. It is limited to focus on meaning with no attention paid to form at all. It means that it excludes attention to the formal elements of the language (Doughty & Williams, 1999). Thus, focus on meaning would be concerned with getting the L2 learners to concentrate solely on understanding the message being conveyed. It does not allow for any attention whatsoever to the linguistic code of the L2. According to Kemendikbud (2013b), the scientific approach include the finding of meaning, organization and structure of an idea or ideas, so that the student learners gradually learn how to organize and conduct research. Scientific approach emphasizes students' ability in discovering knowledge based on experiential learning, laws, principles and generalizations, so it provides an opportunity for the development of higher order thinking skills. Thus students more empowered learners as a subject of study that should play an active role in hunting down the information from the various sources of learning, and teacher educators more as an organizer and facilitator of learning. As a result, grammar should be taught by focusing on meaning. In the 2013 curriculum, the teaching learning process uses scientific approach which has activities such as observing, questioning, experimenting, associating and communicating. It has connection with Genre Based Approach. The materials in 2013 curriculum use Genre Based Approach as a learning focus through understanding of the social function, the text structure elements - linguistic elements based on the level of difficulty, from the simple to the complex. Text structure refers to the ways that authors organize information in text. It can be descriptive text, narrative text and etc. linguistic elements can be defined as grammatical rule or structure. Grammar here is in the stage of modeling of text. It is included in Based Approach in activity to do presentation and practice activities relating to the grammatical feature of the text. It can be concluded that scientific approach and genre based approach interrelated each other to implement teaching learning process in 2013 curriculum. In 2013 curriculum, people are curious about how the teacher implement grammar teaching in classroom. It is the current curriculum, so people have not understood yet how the rule and the system of the curriculum, whether those are the same or not. So, teacher faces burden to determine when and how grammar will be taught. As there as has been no study on this problem, this study attempts to fill in this gap. It was aimed to investigate and to discover how teacher incorporates grammar in following 2013 Curriculum. Based on the background of the study above, the questions of the problem are formulated as follows: Is this incorporation considered focus on form or focus on meaning? Through this kind of incorporation, do the students feel that they have learned English grammar? METHODS In this research, qualitative design was used for some reasons. First, researcher wanted to describe the research with words than numbers. The researcher wanted to know how the teacher interpreted grammar in 2013 curriculum whether it was focus on form or focus on meaning. The researcher also wanted to investigate the feeling of the students, they experienced to learn grammar or not. The subjects of the research were an English teacher and the first graders of SMPN 1 Gresik. There are six English teachers there. The researcher observed one of them and the teacher that the researcher observed was a female teacher. She was chosen as the reason she teaches in the first grade that implement 2013 curriculum. There, there are eight classes of the first grade. The class that the researcher was observed were G and H class. Each class consist of thirty three students. These subjects were chosen under the consideration that the researcher followed the schedule of the teacher and the materials that were she taught. There was no certain choice of class. The most important was the first graders. In SMPN 1 Gresik, 2013 curriculum is now implemented and the teacher has been trained in facing 2013 curriculum. Therefore, the teacher and the first graders were chosen. The material that was observed was descriptive text about things around. The students had to describe things in the picture. They are instructed to make sentences with the correct grammatical construction. For example, they had to know about introductory ‘there’, present tense and present continuous tense. The teacher did not explain generic structure of descriptive text, but she concerned on making sentences based on grammatical rule. The first data was the teacher and student’s action in the classroom. It was done by using video recording that recorded what the teacher and the students did in the classroom. It recorded teacher and student’s activities, what materials that the teacher taught and how the teacher’s way in teaching grammar to the students whether it is focused on meaning or focused on form. It was held on November, 18, 25 and 27 2013 in SMPN 1 Gresik. The video was taken during an hour. After taking video recording, the data was analysed by transcribing it into the words. The second data were the student’s experience in the classroom whether they feel learned grammar or not. The data was collected by doing focused group discussion. It was taken use video recording. The duration was not more than two minutes. Focused group discussion here means that the researcher divided the students into group. There were thirty students in the classroom. The researcher divided them into four groups and each group consist of eight students. The member of group was taken randomly, which is male and female students were mixed. After dividing groups, the researcher began to ask some questions. The questions were semi structured. There were three questions as a foundation, and there were some complement questions to develop the information from the students. The questions are: (1) Kalian tau apa itu grammar? (2) Selama ini sudah belajar grammar? (3) Grammar apa saja? (4) Menurut kalian grammar itu susah atau gampang? (5) Diterangkan langsung atau diterangkan jika kalian ada kesalahan? After collecting the data, the analysis of the data was carried out. The first data was from teacher and students’ action. The teacher’s way of teaching was identified in this study. It was described in the form of transcribes of observation recording. The thing that will be underline was when she incorporates grammar in the class based on 2013 curriculum. To make the process of identification was easier, the area of shows the teacher incorporates grammar was underlined. First, describing. Here, was describe about what teacher did in the classroom, classified what she did into focus on form and or focus on meaning and described the learners did in the classroom when teacher were explaining the material. Second, analyzing and interpreting. The teacher did in the classroom will be analyzed and interpreted here. Besides, it was also include what the learners experienced in the classroom when the lesson was running. Last, is drawing conclusion. It focuses on teacher’s focus of teaching. Whether focus on for and or focus meaning. Whether or not the learners feel learnt. The second data was student’s feeling of experienced in learning grammar or not. The students’ feeling of learned grammar data which were obtained from focused group discussion were analyzed by some procedures. First, transcribing the video recording. It was from the verbation of the students. In other words, it was from students’ utterances when answer the researcher’s question. Second, is coding the data. Here, the researcher coded the data from the transcription. The thing that was underlined was the student’s answer about their feeling in learning grammar whether they feel learned or not. Last, is interpreting the data. The students’ utterances that shown the student’s feeling were interpreted and those are combined with the result of observation. RESULTS AND DISCUSSION It was found that the teacher interpret teaching grammar in the focus on form. These are the examples of sentences that shows focus on form: “Jadi kalau misalnya eraser, window, book, and other we can call the noun”. “So, in this chapter and meeting we will learn about noun, adjective and verbs”. “So, bagaimana cara bertanya, mendeskripsikan benda itu yang akan kita pelajari. Misalnya, Feli I see you have new watch”. “Ok. Umbrella. I have my colorful umbrella. Satu lagi. I love my pink bag. It has beautiful garden. Bisa dilihat disini bagaimana mendeskripsikan things, bagaimana menempatkan adjective”. “Structurenya masih salah ini. Yang benar adalah I love my full color shoes”. “There are many children in a playground. Ok? And there are many people in the market, but in my house there is one person. Ok ya? Paham?”. From three times observations, the teacher was consistent in focused on form. Focus on form means that the students have to aware on grammatical form of the language. It can be as like composing sentences based on the right pattern. It was proven in the explanation above that the teacher gave more explanations about the pattern of present continuous tense, composing sentence based on the right structure about subject, plural and singular, verb and also noun and introductory there. The teacher gave some example of pattern and structure of some grammar to the students. She repeated several times about what she wanted to explain until she thought that the students understand the materials. It also can be seen from the teacher’s activities in the classroom that she walked around the class to check students’ works and explained something that the students did not understand. It showed that the teacher wanted to make students comprehend the pattern based on the grammatical rule. In other word, the teacher interprets grammar teaching by focusing on form. It is found that what the teacher did in the classroom showed that she was interpreting grammar in classroom by focusing on form. It is proven in the result of observation that the teacher teaches grammar by giving the grammatical rule that contains the structure and pattern to compose a sentence. She explained the grammatical rule to the students. The teacher applied it in the classroom maybe as the reason she wants to make the students focus on grammatical rule that can make them compose the sentences in the right pattern. It is in line with the theory of Long (1997) that Focus on form is a method for composing sentence based on the right pattern. It promotes the acquisition of specific language form such as grammar and the meaning of words in the meaning-based second language activity. Doughty & Williams (1999) state that a focus on the form (FonF) of the language consists of drawing the learner's attention to the linguistic features of the language. Thus, a focus on form approach would allow for the second language (L2) learners to concentrate on the grammatical rules and construct of the language. For example, a student is given a text in the L2. He or she would focus on form if they were asked to analyze the text in terms of how it represents the rules of the language. Other reason, she wants to develop the language knowledge and language acquisition. This condition proves the theory from Long & Robinson (1999) that focus on form as an occasional shift of attention to linguistic code features by the teacher and/or one or more students triggered by perceived problems with comprehension or production. He also states that Focus on form is a basis of Interaction Hypothesis and it emphases the importance of interaction between learners and other speakers in order to develop their language knowledge. In the classroom, the students feel something about what they got. For getting the information about what they feel about what they learnt, the researcher make focused group discussion. In the classroom, there are thirty three students. The researcher divided the students into four groups. Each group consists of about eight students. The members of groups were taken randomly. Male and female students were mixed. It depends on the students itself. After dividing groups, the writer began to ask some questions. The questions were semi structured. There were three questions as a foundation, but there were some complement questions to develop the information from the students. The conversation did not take long time. It was not more than two minutes length. The questions are: (1) Kalian tau apa itu grammar? (2) Selama ini sudah belajar grammar? (3) Grammar apa saja? (4) Menurut kalian grammar itu susah atau gampang? (5) Diterangkan langsung atau diterangkan jika kalian ada kesalahan?. From focused group discussion, it can be concluded that not all of students understand what grammar is. From four groups, two groups showed that the members did not know the meaning of grammar and two groups showed that the members know the meaning of it. It is proven in the answer of the second group “Grammar itu apa bu? ak taunya gamer”. The answer of the fourth group is “Pernah denger grammar, tapi gak tau artinya itu apa”. It showed that they have not understood the meaning of grammar. When researcher asked the second question, which is “Selama ini sudah belajar grammar?” the result showed that almost all of students experienced it. They also said that during this semester, they have been taught grammar by the teacher. It is proven in the discussions. “Jadi pernah diajarkan grammar sama Bu Shofa?” “pernah” “Waktu ngajarnya itu Bu shofa langsung diterangkan di depan papan tulis atau berdasarkan kalian baca-baca buku?” “Langsung diterangkan di papan tulis”. But in the third group, there are different answers from members. Some members said that they have been taught grammar, and some members said that they have not been taught grammar yet by the teacher. When the researcher asked what kind of grammar that they have received in this semester, the result showed that during this semester they got some grammar explanations from the teacher. The first group said that they have been taught adjective, pronoun and verb. The second group said that they have been taught Irregular verb. The third group said that they have been taught present tense and continuous tense. The last group feel be taught subject, verb and object. So, it can be concluded that they have been received simple present tense and present continuous tense. After receiving those kinds of materials, they concluded that grammar is easy. It is proven in the result of discussion that each group felt grammar is easy to be learnt. “Menurut kalian, grammar itu gampang apa susah?” The first group said “Gampang”. The second group goup said “Lumayan gampang”. The third group said “Alhamdulillah gampang. The last group said “gampang-gampang susah”. So, it can be concluded that they feel easy to learn grammar and there is no difficulties to received materials. It was also found from focused group discussion that the students feel learned grammar during this semester. The result showed that almost all of students experienced it. They also said that during this semester, they have been taught grammar by the teacher. It is proven in the discussions. “Jadi pernah diajarkan grammar sama Bu Shofa?” “pernah” The result is in line with the theory of Sinclair (2000)’s statement that grammar is easy to understand. He also affirms that grammar is superficially easy to observe. Collins et.al (2009) argue that grammar can be easy and difficult. It depends on input that is received by students. In summary, the result showed that teacher interpreted grammar teaching by focusing on form. It can be seen from the teacher activities in the classroom when the lesson was running. The teacher explained it clearly and concerned on grammatical rule. Long (1991) strengthens this condition by stating that focus on form concern on structures, notions and lexical items where language is treated primarily as an object to be studied and practiced. By seeing the teacher’s activities, it showed that students experienced learned grammar by the teacher. It also can be seen from focused group discussion result. CONCLUSIONS Based on results and discussion, it can be concluded that the teacher interpreted grammar in 2013 curriculum by focusing on form. Focus on form means the students have to aware on grammatical form of the language. It happened in the classroom which the researcher observed, that the teacher explained the materials more clearly to the students based on the construct of language and grammatical rule. She demanded the students to acquired grammar naturally attention on the specific language. It is based on the theory of Long (1991) that it refers the traditional teaching that concern on structures, notions, and lexical items where language is treated primarily as an object to be studied and practiced. The teacher implemented focus on form in grammar teaching probably as a reason she wanted to make her students can compose the sentences with the right pattern. Besides, by interpreting focus on form she expected that her students can develop language knowledge and language acquisition. Another conclusion is that the teacher did not follow the rule of 2013 curriculum. In 2013 curriculum, the approach of teaching learning process is Communicative Language Teaching. Communicative language teaching is an approach to language teaching that emphasize interaction as both the means and the ultimate goal of study. It can be focus on form or focus on meaning. But in 2013 curriculum, it is focus on meaning. REFERENCES Astaman, A. (2010). An analysis of Teaching Writing through Genre Based Approach at SMAN 10 Pekan baru. Menulis bersama Aswir. Retrieved from http://menulisbersamaaswir.blogspot.com/2010/03/analysis-of-teaching-writing-trough.html Callaghan, M. a. J. R. (1988). Teaching Factual Writing a Genre Based Approach, Report on the DSP Literacy Project Metropolitan East Region, NSW Departement of EDucation. Sydney: Metropolitan East disadvantage school program. Collins, L., Trofimovich, P., White, J., Cardoso, W., & Horst, M. (2009). Some Input on the Easy/difficult Grammar Question: An Empirical Study. The Modern Language Journal, 93(3), 336-353. Doughty, C., & Williams, J. (1999). Focus on Form in Classroom Second Language Acquisition. Cambridge: Cambridge University Press. Gao, J. (2007). Teaching Writing in Chinese Universities: Finding an Electric Approach Asian EFL Journal, 20. Kemendikbud. (2013a). Kompetensi Dasar: Kementrian Pendidikan dan Kebudayaan. Kemendikbud. (2013b). Pembelajaran Berbasis Kompetensi Mata Pelajaran Bahasa Inggris Melalui Pendekatan Saintifik. Lin, B. (2006). Genre Based Teaching and Principle in EFL: The Case University Writing Course. Asian EFL Journal 8(3), 226-248. Long. (1997). Focus on form in Task Based Language Teaching. The Mac Graw Hill Companies. Long, M. H. (1991). Focus on form: A Design Features in Language Teaching. Amsterdam: John Benjamins. Long, M. H., & Robinson, P. (1999). Focus on Form: Theory, Research and Practice. Cambridge: Cambridge University Press. Yan, G. (2005). A Process Genre Model for Teaching Writing (Vol. 43): English Teaching Forum.